The midnight ride - Mezrich, Ben, 1969- (Grand Central Publishing, 2022)
"Hailey Gordon is looking to make some fast cash to help pay her tuition when she's caught counting cards at the Encore casino in Boston...and makes her escape. With guards closing in, she dives into an unlocked room to hide...only to find a dead body...Nick Patterson hasn't felt hope in a long time, but the job he 'inherited' in prison promises to change that. He enters hotel room 633 to find that the person he was supposed to meet has been murdered. Next to the corpse stands a terrified young woman--Hailey Gordon"--